The role of customer experience in the omnichannel strategy during the purchasing proces - Castillo-Jiménez, Andrea (2020)
Nowadays, a hyper-connected consumer is not satisfied with using only one channel of everything the brand offers, but rather looks for the diversity of options to make their purchase. This research seeks to analyze how the customer experience is during the purchase process developed in the omnichannel strategy of the department store. The study used qualitative research methods to data gathering and analysis. To best capture customer experience, semi-structured interview, using open-ended questioning, was suited to data gathering. The participants were 13 customers who consented to be interviewed. Recruitment of participants concluded when data saturation occurred. It was evident how the omnichannel strategy works in a synchronized and positive way in the department store, without any interruption to consolidate the purchase.